EFFORTS TO IMPROVE MATHEMATICS LEARNING OUTCOMES USING THE THINK PAIR AND SHARE LEARNING MODEL ASSISTED BY PAIR CARD MEDIA - Witiah, Sindi; Hidayat, Puput Wahyu; Pitra, Dedek Helida (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This study was conducted with the aim of improving mathematics learning outcomes by using the Think Pair and Share learning model assisted by Pair Card media for fifth-grade students at SDN 201/VI Lubuk Napal. This type of research is Classroom Action Research (CAR), in which the researcher acts as the implementer, while the teacher and peers serve as observers. The research design follows the classroom action research model consisting of two cycles. The study was carried out in the even semester of the 2025–2026 academic year. The subjects of the study were 13 fifth-grade students of SDN 201/VI Lubuk Napal. The object of the study was the learning process and students’ learning outcomes. Data collection techniques included observation, testing, and documentation. The data were analyzed descriptively and presented in tables and graphs. The results of the study showed an improvement in both the learning process and learning outcomes. The learning process in Cycle I reached 84.61%, and increased to 100% in Cycle II. As for the learning outcomes, 84.62% of students achieved the learning goal in Cycle I, and this increased to 100% in Cycle II, indicating an improvement of 16.38%. Therefore, the use of the Think Pair and Share learning model assisted by Pair Card media in mathematics lessons can improve both the learning process and learning outcomes of fifth-grade students at SDN 201/VI Lubuk Napal